ANALISIS TREN GAYA HIDUP HEDONISME TERHADAP PERILAKU KONSUMTIF MAHASISWA PROGRAM STUDI EKONOMI DI ERA DIGITAL - Laila Surayya; Tri Handayani; Mariyatul Kubtiyah; Dinda Vebrina; Rosnida Siregar (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The rapid development of digital technology and social media has significantly shifted the lifestyle of young adults, often pushing them toward hedonism and consumptive behavior. This study aims to determine the effect of a hedonistic lifestyle on the consumptive behavior of sixth-semester Economics Study Program students at Institut Pendidikan Tapanuli Selatan. The research addresses a critical gap regarding how students with formal economic education still fall into irrational consumption patterns. This quantitative research used an explanatory approach. From a total population of 52 students, 50 valid responses were collected using a total sampling technique adjusted for data validity. Data were gathered through a modified Likert scale questionnaire and analyzed using simple linear regression with SPSS. The results showed that the hedonistic lifestyle has a very strong and significant positive effect on consumptive behavior, evidenced by a t-count of 16.331 (greater than the t-table of 1.676) and a significance value of 0.000. Furthermore, the coefficient of determination (R-square) reached 0.847, indicating that 84.7% of the variation in student consumptive behavior is driven by hedonistic lifestyle choices. This emphasizes the urgent need for practical financial literacy interventions on campus.